2018
DOI: 10.1080/17290376.2018.1516160
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s not good to eat a candy in a wrapper’: male students’ perspectives on condom use and concurrent sexual partnerships in the eastern Democratic Republic of Congo

Abstract: This paper reports on fieldwork carried out in 2011 with aim to investigate young men’s perspectives about condoms use, concurrent sexual partnerships and sex in the context of HIV/AIDS. This study employed a qualitative approach to collect data from 28 boys aged 16–20 from two urban and two rural high schools in South Kivu province. Four focus group discussions and 20 individual interviews were conducted among them. The findings showed that most students identified condoms as unsafe and untrustworthy. Reasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(41 citation statements)
references
References 69 publications
(101 reference statements)
0
41
0
Order By: Relevance
“…15,[17][18][19] In many low and middle income countries (LMICs), there are powerful social and symbolic meanings attached to condoms, which discourage young people from using them, including the association of condoms with disease, immorality and promiscuity. 18,[20][21][22][23][24] As such, 'using a condom is not a simple physical actit also has social meaning'. 18 Understanding the contextual influences on condom use and how these connect with sexual health, risk-reduction practices and access to health services can enhance the design and delivery of more appropriate SRH care for young people.…”
Section: Introductionmentioning
confidence: 99%
“…15,[17][18][19] In many low and middle income countries (LMICs), there are powerful social and symbolic meanings attached to condoms, which discourage young people from using them, including the association of condoms with disease, immorality and promiscuity. 18,[20][21][22][23][24] As such, 'using a condom is not a simple physical actit also has social meaning'. 18 Understanding the contextual influences on condom use and how these connect with sexual health, risk-reduction practices and access to health services can enhance the design and delivery of more appropriate SRH care for young people.…”
Section: Introductionmentioning
confidence: 99%
“… Between 32 and 48 14–20 Moyo & Rusinga, 2017 [ 52 ] Qualitative To understand the importance of reproductive health education to contraceptive use among adolescents Zimbabwe A total of 185 adolescents aged 15–19 years were sampled. 96 89 185 15–19 (mean 17) Mulumeoderhwa, 2018 [ 53 ] Qualitative To investigate young men’s perspectives about condom use, concurrent sexual partnerships and sex in the context of HIV/AIDS. Democratic Republic of Congo 28 boys aged 16–20 from two urban and two urban high schools in South Kivu provinces.…”
Section: Resultsmentioning
confidence: 99%
“…Key finding: A minority of studies reported positive attitudes towards condom use as a facilitator of condom use. - Twenty studies reported negative attitudes about condoms and condom use with the central attitudes being they are ineffective [ 38 , 39 , 41 , 45 , 52 , 53 , 57 ], cause disease [ 43 , 51 , 53 , 56 , 57 ], reduced sexual pleasure for men [ 39 , 40 , 42 , 44 , 45 , 47 , 53 , 56 , 57 ], are morally inferior to abstinence outside of marriage [ 41 , 53 , 59 ], and represent a lack of trust in committed and transactional relationships [ 37 , 41 , 42 , 44 , 46 49 , 54 , 59 ]. - Two studies did report positive attitudes to condoms (generally related to their value in preventing STIs and unintended pregnancy) [ 43 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also some studies have suggested that specific interventions are needed to improve the utilisation of HIV testing amongst heterosexual drug users, particularly amongst non-injection drug users since they are at very high risk of HIV transmission [31]. A study carried out in Congo about male students' perspectives on condom use and concurrent sexual partnerships revealed low knowledge about prevention of sexually transmitted infection since majority of students said that they prefer flesh to flesh sex than using condom and this seems prevalent among school students [32].…”
Section: Introductionmentioning
confidence: 99%